2010
DOI: 10.1080/10426910903365752
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Fabrication Process of Porous Metal Fiber Sintered Felts with Three-Dimensional Reticulated Structure

Abstract: A novel porous metal fiber sintered felt (PMFSF) with a three-dimensional reticulated structure has been produced by the solid-state sintering of copper fibers. The copper fibers, with several microstructures distributed onto the surface, were fabricated using the cutting method. The Scanning Electron Microscope (SEM) results revealed that there were two kinds of sintering joints present in the PMFSFs: fiber-to-fiber surface contact and crossing fiber meshing. In the sintering process, the surface microstructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…4. As shown in the previous work [15], we could found that there were two kinds of sintering joints present in the PMFSS including point to point contact and fiber to fiber surface contact. And these two kinds of sintering joints formed two kinds of pore structures; they are point pore structure and long strip pore structure, as shown in Fig.4a and 4b, respectively.…”
Section: Resultsmentioning
confidence: 83%
“…4. As shown in the previous work [15], we could found that there were two kinds of sintering joints present in the PMFSS including point to point contact and fiber to fiber surface contact. And these two kinds of sintering joints formed two kinds of pore structures; they are point pore structure and long strip pore structure, as shown in Fig.4a and 4b, respectively.…”
Section: Resultsmentioning
confidence: 83%
“…The PMFSF was manufactured in four steps [34]: (1) As shown in Fig. 3 (a), the continuous copper fibers with an equivalent diameter of 150 lm were fabricated by cutting with a multi-tooth tool.…”
Section: Manufacturing Mf-pcmmentioning
confidence: 99%
“…However, the surface of these stainless-steel fibers were smooth, which couldn't fully promote the heat communication between PCM and the fibers. The copper fibers fabricated by cutting with a multi-tooth tool [34] have a large number of antler microstructures on their surface. These surface microstructures help enlarge the specific surface area of the PMFSF and accelerate the turbulent flow of liquid PCM, both of which enhance the thermal communication between PCM and PMFSF.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the porosity of PMFSS is known in advance during manufacture using the mass-volume method as follows [1]:…”
Section: Morphology Analysis Of Pmfssmentioning
confidence: 99%
“…Porous Metal Fiber Sintered Sheet (PMFSS), a new kind of functional porous material, has been successfully produced recently and proved to be promising [1]. It has interconnected high porosity, large specific surface, and good mechanical strength [2].…”
Section: Introductionmentioning
confidence: 99%